Effect of Fertilizer SP-36 and Green Tonic Fertliser Aplication on the Growth and Yield of Been Plant (Phaseolus vulgaris L) Perkasa Variety - Diki Kriswanto (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
The aim of this research  is to know  effect of SP-36 fertilizer and  liquid green tonic fertilizer on the growth and yield of green  been plants. The study  was conducted from February 2017 until May 2017. The located of the recearch at Barong Tongkok Village, Subdistrict, Kutai Barat Recency. The receach design used Completely Randomized Design (RAL) in experimental factorial pattern 4 x 4 with 3 replications. Factor I : dosage of SP-36 fertilizer (P), consisting  of 4 levels, namely : No SP-36 aplication or control (p0), SP-36 4 g /polibag (p1), SP-36 6 g/polibag  (p2), and SP-36 8 g/polibag (p3). Factor II : Concentration of Green Tonic Fertilizer (G), consisting of 4 levels, namely : No green tonic fertilizer or control (g0), green tonic 2 ml / polibag (g1), green tonic  4 ml/polibag(g2) , and green tonic 6 ml/ polibag (g3).The result showed that SP-36 fertilizer treatment had no signfiicant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, long of fruit , ammount of  fruit,  and fruit weight per crop.The treatment of green tonic fertilizer had  no significant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, length of fruit , number of  fruit,  and fruit weight per crop.The interaction treatment had no significant effect on the plant length at 10, 20, and 30 days after planting, age of flower emerged, long of fruit , ammount of  fruit,  and fruit weight per crop.